Inhibitory effects of Manihot esculenta extracts on food-borne pathogens and their antioxidant properties: supercritical fluid extraction, statistical analysis, and molecular docking study - Ahmad, Mohammad Norazmi; Mohd Azli, Nur Hidayah; Ismail, Hakimah; Mohamed Iqbal, Mohammad Anwar; Mat Piah, Mohd Bijarimi; Abdullah, Erna Normaya (Blackwell Publishing Inc., 2020)
Abstract An alternative natural additive from Manihot esculenta has been recently discovered. Using a response surface methodology (RSM) approach, a high content of antioxidant activity based on DPPH inhibition from the plant source was found, with the optimum production conditions being 45.9C, 4,100 psi, and 44 min for temperature, pressure, and time, respectively. The optimized extract was analyzed using gas chromatography–mass spectrometry (GC–MS), Fourier-transform infrared spectroscopy (FTIR), and UV–Vis spectroscopy. Based on the GC–MS result, the optimized extract contains two major compounds, namely, hexadecanoic acid (40.43%) and 9-octadecenoic acid (32.75%). The optimized extract also showed good activity in inhibiting Bacillus cereus (9.9 ± 0.17 mm) and Escherichia coli (10.7 ± 0.18 mm). To verify the activity of these two compounds toward B. cereus and E. coli, a theoretical approach with molecular docking was used. These two compounds demonstrated good binding affinity toward 2HUC and 1L8A proteins and could be isolated for use as alternative additives in the food industry.